Розробка елементів системи управління якістю машинобудівного підприємства - Варченко, М. А.; Запотроєв, Д. І. (ХНУРЕ, 2021)
The system objects for quality management at machine-building enterprise. Developed activities for development, metrology expertise, quality assessment developed technical documentation for the wheel - shaft, it is estimated the impact of technological process on the quality of finished products, proposed statistical methods for quality control of manufactured production, developed a quality manual. Object of study – the elements of quality management system the machine enterprise. Purpose – to improve the quality of products.
Keywords: управління якістю